On the Influence of Artificial Intelligence on Foreign Language Learning and Suggested Learning Strategies - Yang Aijun (International Journal of Education and Humanities, 2024)
In recent years, the integration of artificial intelligence (AI) technologies in education, particularly in foreign language acquisition, has seen significant growth, leading to notable improvements. This paper explores the potential of AI to enhance the efficiency of foreign language learning through personalized learning, interactive practice, real-time feedback, diagnostic evaluation, flexible learning paths, cultural immersion, and efficient learning strategies. Additionally, it addresses concerns regarding over-reliance on technology, potential negative impacts on self-learning abilities, diminished interpersonal communication and cultural understanding, limitations of personalized education, technical challenges and reliability issues, as well as ethical considerations such as data privacy. Furthermore, the paper highlights the risk of marginalizing the role of human teachers in the learning process. Drawing on both positive and negative impacts of AI in foreign language learning, the paper concludes by offering suggestions for effective language learning strategies